Internal marketing and employees commitment towards organization: case study of Dewan Bandaraya Kuching Utara (DBKU) / Andy Nen - Nen, Andy (2005)
The purposes of this research is to determine the internal marketing and employee’s commitment of Dewan Bandaraya Kuching Utara (DBKU) and also to analyze the possible factors that can improve the employee’s commitment to Dewan Bandaraya Kuching Utara (DBKU) through good internal marketing so the employees and organization can go together to achieving the vision of the organization. The result in section B and C show that majority of the respondents which are 100 respondents said that the level of satisfaction towards DBKU are agreed and satisfy. The respondent’s level of the commitment also give a majority result said agreed beside only statement for better offer for other job are not agreed. The result also show that the internal marketing in DBKU can be improving by improving the motivation and satisfaction to the employees, improving the internal marketing system in DBKU, practice effectively the internal marketing and also work efficiently with the employees about internal marketing.